6.107 Problems 10601 to 10700

Table 6.213: Main lookup table sequentially arranged

#

ODE

Mathematica

Maple

10601

\[ {}y^{\prime } = \frac {x}{-y+F \left (x^{2}+y^{2}\right )} \]

10602

\[ {}y^{\prime } = \frac {F \left (\frac {y^{2} a +b \,x^{2}}{a}\right ) x}{\sqrt {a}\, y} \]

10603

\[ {}y^{\prime } = \frac {6 x^{3}+5 \sqrt {x}+5 F \left (y-\frac {2 x^{3}}{5}-2 \sqrt {x}\right )}{5 x} \]

10604

\[ {}y^{\prime } = \frac {F \left (y^{{3}/{2}}-\frac {3 \,{\mathrm e}^{x}}{2}\right ) {\mathrm e}^{x}}{\sqrt {y}} \]

10605

\[ {}y^{\prime } = \frac {F \left (-\frac {-y^{2}+b}{x^{2}}\right ) x}{y} \]

10606

\[ {}y^{\prime } = \frac {F \left (\frac {x y^{2}+1}{x}\right )}{y x^{2}} \]

10607

\[ {}y^{\prime } = \frac {-2 x^{2}+x +F \left (y+x^{2}-x \right )}{x} \]

10608

\[ {}y^{\prime } = \frac {2 a}{x^{2} \left (-y+2 F \left (\frac {x y^{2}-4 a}{x}\right ) a \right )} \]

10609

\[ {}y^{\prime } = \frac {y+F \left (\frac {y}{x}\right )}{x -1} \]

10610

\[ {}y^{\prime } = \frac {-x +F \left (x^{2}+y^{2}\right )}{y} \]

10611

\[ {}y^{\prime } = \frac {F \left (-\frac {-1+2 y \ln \left (x \right )}{y}\right ) y^{2}}{x} \]

10612

\[ {}y^{\prime } = \frac {F \left (-\left (x -y\right ) \left (x +y\right )\right ) x}{y} \]

10613

\[ {}y^{\prime } = \frac {y^{2} \left (2+F \left (\frac {x^{2}-y}{y x^{2}}\right ) x^{2}\right )}{x^{3}} \]

10614

\[ {}y^{\prime } = \frac {2 F \left (y+\ln \left (2 x +1\right )\right ) x +F \left (y+\ln \left (2 x +1\right )\right )-2}{2 x +1} \]

10615

\[ {}y^{\prime } = \frac {2 y^{3}}{1+2 F \left (\frac {1+4 x y^{2}}{y^{2}}\right ) y} \]

10616

\[ {}y^{\prime } = -\frac {y^{2} \left (2 x -F \left (-\frac {x y-2}{2 y}\right )\right )}{4 x} \]

10617

\[ {}y^{\prime } = -\left (-{\mathrm e}^{-x^{2}}+x^{2} {\mathrm e}^{-x^{2}}-F \left (y-\frac {x^{2} {\mathrm e}^{-x^{2}}}{2}\right )\right ) x \]

10618

\[ {}y^{\prime } = \frac {2 y+F \left (\frac {y}{x^{2}}\right ) x^{3}}{x} \]

10619

\[ {}y^{\prime } = \frac {\sqrt {y}}{\sqrt {y}+F \left (\frac {x -y}{\sqrt {y}}\right )} \]

10620

\[ {}y^{\prime } = \frac {-3 x^{2} y+F \left (x^{3} y\right )}{x^{3}} \]

10621

\[ {}y^{\prime } = \frac {y+F \left (\frac {y}{x}\right ) x^{2}}{x} \]

10622

\[ {}y^{\prime } = \frac {-2 x -y+F \left (x \left (x +y\right )\right )}{x} \]

10623

\[ {}y^{\prime } = \frac {\left (y \,{\mathrm e}^{-\frac {x^{2}}{4}} x +2 F \left (y \,{\mathrm e}^{-\frac {x^{2}}{4}}\right )\right ) {\mathrm e}^{\frac {x^{2}}{4}}}{2} \]

10624

\[ {}y^{\prime } = \frac {x +y+F \left (-\frac {-y+x \ln \left (x \right )}{x}\right ) x^{2}}{x} \]

10625

\[ {}y^{\prime } = \frac {x \left (a -1\right ) \left (a +1\right )}{y+F \left (\frac {y^{2}}{2}-\frac {a^{2} x^{2}}{2}+\frac {x^{2}}{2}\right ) a^{2}-F \left (\frac {y^{2}}{2}-\frac {a^{2} x^{2}}{2}+\frac {x^{2}}{2}\right )} \]

10626

\[ {}y^{\prime } = \frac {y}{x \left (-1+F \left (x y\right ) y\right )} \]

10627

\[ {}y^{\prime } = -\frac {-x^{2}+2 x^{3} y-F \left (\left (x y-1\right ) x \right )}{x^{4}} \]

10628

\[ {}y^{\prime } = \frac {F \left (\frac {\left (3+y\right ) {\mathrm e}^{\frac {3 x^{2}}{2}}}{3 y}\right ) x y^{2} {\mathrm e}^{3 x^{2}} {\mathrm e}^{-\frac {9 x^{2}}{2}}}{9} \]

10629

\[ {}y^{\prime } = \frac {\left (1+y\right ) \left (\left (y-\ln \left (1+y\right )-\ln \left (x \right )\right ) x +1\right )}{y x} \]

10630

\[ {}y^{\prime } = \frac {6 y}{8 y^{4}+9 y^{3}+12 y^{2}+6 y-F \left (-\frac {y^{4}}{3}-\frac {y^{3}}{2}-y^{2}-y+x \right )} \]

10631

\[ {}y^{\prime } = \frac {y^{2}+2 x y+x^{2}+{\mathrm e}^{2 F \left (-\left (x -y\right ) \left (x +y\right )\right )}}{y^{2}+2 x y+x^{2}-{\mathrm e}^{2 F \left (-\left (x -y\right ) \left (x +y\right )\right )}} \]

10632

\[ {}y^{\prime } = \frac {1}{y+\sqrt {x}} \]

10633

\[ {}y^{\prime } = \frac {1}{y+2+\sqrt {1+3 x}} \]

10634

\[ {}y^{\prime } = \frac {x^{2}}{y+x^{{3}/{2}}} \]

10635

\[ {}y^{\prime } = \frac {x^{{5}/{3}}}{y+x^{{4}/{3}}} \]

10636

\[ {}y^{\prime } = \frac {i x^{2} \left (i-2 \sqrt {-x^{3}+6 y}\right )}{2} \]

10637

\[ {}y^{\prime } = \frac {x}{y+\sqrt {x^{2}+1}} \]

10638

\[ {}y^{\prime } = \frac {\left (-1+y \ln \left (x \right )\right )^{2}}{x} \]

10639

\[ {}y^{\prime } = \frac {x \left (-2+3 \sqrt {x^{2}+3 y}\right )}{3} \]

10640

\[ {}y^{\prime } = \frac {\left (-1+2 y \ln \left (x \right )\right )^{2}}{x} \]

10641

\[ {}y^{\prime } = \frac {{\mathrm e}^{b x}}{y \,{\mathrm e}^{-b x}+1} \]

10642

\[ {}y^{\prime } = \frac {x^{2} \left (1+2 \sqrt {x^{3}-6 y}\right )}{2} \]

10643

\[ {}y^{\prime } = \frac {{\mathrm e}^{x}}{y \,{\mathrm e}^{-x}+1} \]

10644

\[ {}y^{\prime } = \frac {{\mathrm e}^{\frac {2 x}{3}}}{y \,{\mathrm e}^{-\frac {2 x}{3}}+1} \]

10645

\[ {}y^{\prime } = \frac {1+2 x^{5} \sqrt {1+4 x^{2} y}}{2 x^{3}} \]

10646

\[ {}y^{\prime } = \frac {x \left (x +2 \sqrt {x^{3}-6 y}\right )}{2} \]

10647

\[ {}y^{\prime } = \left (-\ln \left (y\right )+x^{2}\right ) y \]

10648

\[ {}y^{\prime } = \frac {{\mathrm e}^{-x^{2}} x}{y \,{\mathrm e}^{x^{2}}+1} \]

10649

\[ {}y^{\prime } = -\left (-\ln \left (\ln \left (y\right )\right )+\ln \left (x \right )\right ) y \]

10650

\[ {}y^{\prime } = \left (-\ln \left (\ln \left (y\right )\right )+\ln \left (x \right )\right )^{2} y \]

10651

\[ {}y^{\prime } = \frac {y}{\ln \left (\ln \left (y\right )\right )-\ln \left (x \right )+1} \]

10652

\[ {}y^{\prime } = \frac {1+2 \sqrt {1+4 x^{2} y}\, x^{4}}{2 x^{3}} \]

10653

\[ {}y^{\prime } = \frac {\left (-y^{2}+4 a x \right )^{2}}{y} \]

10654

\[ {}y^{\prime } = \frac {x \left (-2+3 x \sqrt {x^{2}+3 y}\right )}{3} \]

10655

\[ {}y^{\prime } = -\frac {x^{2} \left (a x -2 \sqrt {a \left (a \,x^{4}+8 y\right )}\right )}{2} \]

10656

\[ {}y^{\prime } = \left (-\ln \left (y\right )+x \right ) y \]

10657

\[ {}y^{\prime } = \frac {x^{3}+x^{2}+2 \sqrt {x^{3}-6 y}}{2+2 x} \]

10658

\[ {}y^{\prime } = \frac {\left (y^{2} a +b \,x^{2}\right )^{2} x}{a^{{5}/{2}} y} \]

10659

\[ {}y^{\prime } = -\frac {x^{3} \left (x \sqrt {a}+\sqrt {a}-2 \sqrt {a \,x^{4}+8 y}\right ) \sqrt {a}}{2 \left (1+x \right )} \]

10660

\[ {}y^{\prime } = -\frac {x}{4}+\frac {1}{4}+x \sqrt {x^{2}+8 y-2 x +1} \]

10661

\[ {}y^{\prime } = -\frac {x}{2}-\frac {a}{2}+x \sqrt {x^{2}+2 a x +a^{2}+4 y} \]

10662

\[ {}y^{\prime } = \frac {\left (\ln \left (y\right )+x^{2}\right ) y}{x} \]

10663

\[ {}y^{\prime } = \frac {2 a +x \sqrt {-y^{2}+4 a x}}{y} \]

10664

\[ {}y^{\prime } = -\frac {x}{2}+1+x \sqrt {x^{2}-4 x +4 y} \]

10665

\[ {}y^{\prime } = -\frac {2 x^{2}+2 x -3 \sqrt {x^{2}+3 y}}{3 \left (1+x \right )} \]

10666

\[ {}y^{\prime } = \frac {y^{3} {\mathrm e}^{-\frac {4 x}{3}}}{y \,{\mathrm e}^{-\frac {2 x}{3}}+1} \]

10667

\[ {}y^{\prime } = \frac {\left (\ln \left (y\right )+x^{3}\right ) y}{x} \]

10668

\[ {}y^{\prime } = -\frac {x}{4}+\frac {1}{4}+x^{2} \sqrt {x^{2}+8 y-2 x +1} \]

10669

\[ {}y^{\prime } = -\frac {x^{2}-1-4 \sqrt {x^{2}+8 y-2 x +1}}{4 \left (1+x \right )} \]

10670

\[ {}y^{\prime } = -\frac {a x}{2}-\frac {b}{2}+x \sqrt {a^{2} x^{2}+2 a b x +b^{2}+4 a y-4 c} \]

10671

\[ {}y^{\prime } = -\frac {x}{2}-\frac {a}{2}+x^{2} \sqrt {x^{2}+2 a x +a^{2}+4 y} \]

10672

\[ {}y^{\prime } = -\frac {a x}{2}-\frac {b}{2}+x^{2} \sqrt {a^{2} x^{2}+2 a b x +b^{2}+4 a y-4 c} \]

10673

\[ {}y^{\prime } = \frac {x}{2}+\frac {1}{2}+x^{2} \sqrt {x^{2}-4 y+2 x +1} \]

10674

\[ {}y^{\prime } = \frac {2 a +x^{2} \sqrt {-y^{2}+4 a x}}{y} \]

10675

\[ {}y^{\prime } = -\frac {x}{2}+1+x^{2} \sqrt {x^{2}-4 x +4 y} \]

10676

\[ {}y^{\prime } = -\frac {\left (\sqrt {a}\, x^{4}+\sqrt {a}\, x^{3}-2 \sqrt {a \,x^{4}+8 y}\right ) \sqrt {a}}{2 \left (1+x \right )} \]

10677

\[ {}y^{\prime } = \left (-\ln \left (y\right )+1+x^{2}+x^{3}\right ) y \]

10678

\[ {}y^{\prime } = \frac {y^{3} {\mathrm e}^{-2 b x}}{y \,{\mathrm e}^{-b x}+1} \]

10679

\[ {}y^{\prime } = \frac {y^{3} {\mathrm e}^{-2 x}}{y \,{\mathrm e}^{-x}+1} \]

10680

\[ {}y^{\prime } = \frac {\left (-2 y^{{3}/{2}}+3 \,{\mathrm e}^{x}\right )^{2} {\mathrm e}^{x}}{4 \sqrt {y}} \]

10681

\[ {}y^{\prime } = \frac {i x \left (i-2 \sqrt {-x^{2}+4 \ln \left (a \right )+4 \ln \left (y\right )}\right ) y}{2} \]

10682

\[ {}y^{\prime } = \frac {\left (x y^{2}+1\right )^{2}}{y x^{4}} \]

10683

\[ {}y^{\prime } = \frac {x^{2} \left (3 x +\sqrt {-9 x^{4}+4 y^{3}}\right )}{y^{2}} \]

10684

\[ {}y^{\prime } = \frac {-\sin \left (2 y\right )+\cos \left (2 y\right ) x^{2}+x^{2}}{2 x} \]

10685

\[ {}y^{\prime } = -\frac {x^{2}-x -2-2 \sqrt {x^{2}-4 x +4 y}}{2 \left (1+x \right )} \]

10686

\[ {}y^{\prime } = \frac {y+x^{3} a \,{\mathrm e}^{x}+a \,x^{4}+a \,x^{3}-x y^{2} {\mathrm e}^{x}-x^{2} y^{2}-x y^{2}}{x} \]

10687

\[ {}y^{\prime } = \frac {x +1+2 x^{6} \sqrt {1+4 x^{2} y}}{2 x^{3} \left (1+x \right )} \]

10688

\[ {}y^{\prime } = \frac {y+x^{3} a \ln \left (1+x \right )+a \,x^{4}+a \,x^{3}-x y^{2} \ln \left (1+x \right )-x^{2} y^{2}-x y^{2}}{x} \]

10689

\[ {}y^{\prime } = \frac {x^{2} \left (x +1+2 x \sqrt {x^{3}-6 y}\right )}{2+2 x} \]

10690

\[ {}y^{\prime } = \frac {y+x^{3} \ln \left (x \right )+x^{4}+x^{3}+7 x y^{2} \ln \left (x \right )+7 x^{2} y^{2}+7 x y^{2}}{x} \]

10691

\[ {}y^{\prime } = \frac {x^{2}+2 x +1+2 \sqrt {x^{2}-4 y+2 x +1}}{2+2 x} \]

10692

\[ {}y^{\prime } = \frac {y+x^{3} b \ln \left (\frac {1}{x}\right )+x^{4} b +b \,x^{3}+x a y^{2} \ln \left (\frac {1}{x}\right )+a \,x^{2} y^{2}+a x y^{2}}{x} \]

10693

\[ {}y^{\prime } = \frac {2 a}{x \left (-x y+2 a x y^{2}-8 a^{2}\right )} \]

10694

\[ {}y^{\prime } = \frac {y \left (-1+\ln \left (x \left (1+x \right )\right ) y x^{4}-\ln \left (x \left (1+x \right )\right ) x^{3}\right )}{x} \]

10695

\[ {}y^{\prime } = \frac {y+\sqrt {x^{2}+y^{2}}\, x^{2}}{x} \]

10696

\[ {}y^{\prime } = \frac {y+\ln \left (\left (x -1\right ) \left (1+x \right )\right ) x^{3}+7 \ln \left (\left (x -1\right ) \left (1+x \right )\right ) x y^{2}}{x} \]

10697

\[ {}y^{\prime } = \frac {y^{3} x \,{\mathrm e}^{2 x^{2}}}{y \,{\mathrm e}^{x^{2}}+1} \]

10698

\[ {}y^{\prime } = \frac {y-\ln \left (\frac {1+x}{x -1}\right ) x^{3}+\ln \left (\frac {1+x}{x -1}\right ) x y^{2}}{x} \]

10699

\[ {}y^{\prime } = \frac {y+{\mathrm e}^{\frac {1+x}{x -1}} x^{3}+{\mathrm e}^{\frac {1+x}{x -1}} x y^{2}}{x} \]

10700

\[ {}y^{\prime } = \frac {x y-y-{\mathrm e}^{1+x} x^{3}+{\mathrm e}^{1+x} x y^{2}}{\left (x -1\right ) x} \]